Transition Time to Full Oral Feeding Skill and Its Determinants in Very Preterm Infants: A Single Center Experience - İlkay Er; Ayla Günlemez (Galenos Yayinevi, 2021)
Aim:Transition from tube to full oral feeding (FOF) represents an important milestone for very preterm infants, and can be affected by various factors. This study aimed to evaluate transition time to FOF in very preterm infants and to identify the factors affecting this ability.Materials and Methods:In this 4-year study, infants' characteristics, feeding steps, and comorbidities were retrospectively evaluated. Infants were categorized into two groups based on FOF timing and comparisons were made. Logistic regression analysis was used to examine any affecting factors.Results:Transition from tube to FOF occurred on a median of 20 days. There were 48 and 52 neonates in the ≤20 days and >20 days groups, respectively. Gender, delivery type, and antenatal history were similar between the groups. The majority were supported with formula. More infants were at >30 weeks of gestational age, and had a birth weight >1.47 kg in the ≤20 days group. A lesser proportion of these required invasive interventions, and had comorbidities. In this study, the requirement of non-invasive ventilation ≤3 days, receiving kangaroo mother care, the promotion of non-nutritive sucking within the first week, and the achievement of full enteral feeding in ≤14 days were associated with a positive effect on the transition to FOF in ≤20 days. However, a gestational age of ≤30 weeks and diagnosis of bronchopulmonary dysplasia had a negative effect.Conclusion:This was one of the few studies to investigate the timing of transition to FOF in very preterm infants as well as its affecting factors. Further studies are required to provide guidance on interventions to shorten FOF time and to provide kangaroo mother care, non-nutritive sucking and breastfeeding in the very preterm population.